1991
DOI: 10.1042/cs0800443
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with nasal continuous positive airway pressure on atrial natriuretic peptide and arginine vasopressin release during sleep in patients with obstructive sleep apnoea

Abstract: 1. Patients with obstructive sleep apnoea have increased diuresis during sleep, which decreases with nasal continuous positive airway pressure treatment. These changes have been attributed to an increased release of atrial natriuretic peptide in obstructive sleep apnoea, and its decrease with continuous positive airway pressure treatment. 2. In order to clarify the change in plasma atrial natriuretic peptide level and to investigate the underlying mechanisms, blood samples were taken at 10 min intervals from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
2
8

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 0 publications
3
51
2
8
Order By: Relevance
“…In spite of the evident acute effects on blood pressure surges with nCPAP, a continued reduction in either nocturnal or diurnal blood pressure may be apparent only in hypertensive OSAS patients and not in normotensive patients, probably in relation to the pressor effect of decreased levels of atrial natriuretic peptide induced by nCPAP application despite the reduction in sympathetic drive. 41 The results of the present study do not allow us to determine whether longer therapy with nCPAP might result in a more significant reversal of diastolic abnormalities in OSAS patients. This could be possible, especially in OSAS patients with left ventricular hypertrophy, in view of the information reported by Cloward et al 37 with regression of ventricular hypertrophy after a minimum of 6 months with nCPAP.…”
Section: Discussionmentioning
confidence: 38%
“…In spite of the evident acute effects on blood pressure surges with nCPAP, a continued reduction in either nocturnal or diurnal blood pressure may be apparent only in hypertensive OSAS patients and not in normotensive patients, probably in relation to the pressor effect of decreased levels of atrial natriuretic peptide induced by nCPAP application despite the reduction in sympathetic drive. 41 The results of the present study do not allow us to determine whether longer therapy with nCPAP might result in a more significant reversal of diastolic abnormalities in OSAS patients. This could be possible, especially in OSAS patients with left ventricular hypertrophy, in view of the information reported by Cloward et al 37 with regression of ventricular hypertrophy after a minimum of 6 months with nCPAP.…”
Section: Discussionmentioning
confidence: 38%
“…In the literature there are studies reporting an association between obesity and increased frequency of nocturia in patients with OSA (12,13,16,18). In our study, although patients with moderate and severe OSA had increased body mass index and neck circumferences, we failed to demonstrate any effect of these parameters on the frequency of nocturia.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, it has been shown that as the severity of OSA increases, the frequency of nocturia increases, as well (6,8). Interestingly, the frequency of nocturia tends to decrease when OSA is treated with continuous positive airway pressure (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] CPAP treatment reduces atrial natriuretic peptide secretion and sodium excretion. 32,34,35 Thus, the pressor effects of increased sodium retention might oppose the expected blood pressure-lowering effects of reduced sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%